The cool companion of AA Doradus-Brown dwarf or late M star? - Mueller, S.; Geier, Stephan; Heber, Ulrich (Astrophysics and Space Science, 2010)
AA Dor is one of only seven known eclipsing binaries consisting of a hot subdwarf star and a low-mass companion. Although AA Dor has been studied in many investigations, a controversy about the nature of its companion persists. Is it a brown dwarf or a low-mass main sequence star?We reanalyse high resolution spectra using metal enhanced LTE model atmospheres. The optical spectra are polluted by reflected light from the companion. Using spectra taken during secondary eclipse, we derive atmospheric parameters consistent with results from the light curve. For the first time we achieve a self-consistent solution that matches all available observations, i.e. the light and radial velocity curves, as well as the atmospheric parameters.The resulting masses M-1 = 0.510(-0.108)(+0.125) M-circle dot and M-2 = 0.085(-0.023)(+0.031) M-circle dot are consistent with the canonical mass of an sdB star and a low-mass main sequence star. However, a brown dwarf companion cannot be excluded.
Keywords: Stars: binaries: close; Binaries: eclipsing; Stars: atmospheres; Stars: individual: AA Dor